Created equal [videorecording (DVD)] - Brown, R. A.; Farquhar, Kurt (Vision Films, 2018)
When Alejandra Batista is rejected in her bid to become a Catholic priest, attorney Tommy Reilly agrees to sue the Archdiocese of New Orleans on her behalf, challenging Judge Watford to choose between Catholic tradition and breaking with convention.